Sulfur/Nitrogen Co‐Doped In‐Plane Porous Carbon Nanosheets as Superior Anode of Potassium‐Ion Batteries. Issue 5 (9th February 2022) - Li, Guilan; Xu, Anding; Zhong, Fulan; Huang, Chuyun; Sun, Hao; Xu, Zhiguang; Wu, Songping; Yan, Yurong
Abstract: Carbonaceous materials are regarded as prospective anode candidates of potassium‐ion batteries. However, the rate capability and cycling stability of classic carbon materials are still far from satisfactory. Herein, we exploit a facile and low‐cost strategy to enable the precise synthesis of sulfur/nitrogen co‐doped in‐plane porous carbon nanosheets with fishnet‐shaped microstructure (SN‐CNSs). The well‐designed in‐plane porous structure and the interconnected carbon flake network can accelerate the diffusion of potassium ions, alleviate volume expansion, and provide sufficient active sites. As a result, the SN‐CNSs deliver an impressively reversible capacity of 248 mAh g −1 at a current density of 1 A g −1 after 4500 cycles, and an excellent rate capacity of 137.3 mAh g −1 after 4000 cycles under 5 A g −1 . Density functional theory (DFT) calculations further verify the advantage of S/N co‐doping in the adsorption/diffusion of K‐ion in SN‐CNSs materials. Such an excellent performance shows that SN‐CNSs possess a great potential to be a superior anode of potassium‐ion batteries. Abstract : For potassium‐ion storage : A facile and low‐cost strategy is exploited to enable the precise synthesis of sulfur/nitrogen co‐doped in‐plane porous carbon nanosheets with fishnet‐shaped microstructure. The well‐designed in‐plane porous structure and the interconnected carbon flake network can accelerate the adsorption/diffusion of potassium ions, alleviate volume expansion, and provide sufficient active sites, rendering such an excellent performance as anode of potassium‐ion batteries.